ETOS KERJA DAN SEMANGAT KAPITALISME DALAM DUNIA KONTEMPORER - Fatimah; Suparman; Arsyad Genda (Istiqra: jurnal hasil penelitian, 2025)
This article examines the relevance of Max Weber’s work ethic in contemporary capitalism, focusing on the transformation of work values in the digital and globalization era. In The Protestant Ethic and the Spirit of Capitalism, Weber argues that modern capitalism developed from the internalization of Protestant religious values, which emphasize discipline, rationality, and efficiency in work. This article examines how the work ethic, which initially supported industrial capitalism, has undergone significant transformations amid the gig economy and flexible work arrangements. Using a qualitative, discursive approach, this article also identifies a shift in the work paradigm, from a high-productivity orientation to a search for work-life balance and individual well-being. Furthermore, this article analyzes the phenomena of burnout and capitalist expectations of workers, as well as alternative movements such as slow work and the post-work society, which offer resistance to an increasingly exploitative work system. In conclusion, although Weber predicted that capitalism would lead to an “iron cage” of rationality, the contemporary world shows the potential to build more balanced and humane working relationships by adapting the spirit of capitalism to the social needs and welfare of workers